DESENTRALISASI FISKAL DAN PENCIPTAAN STABILITAS KEUANGAN DAERAH - Haryanto, Joko Tri; Astuti, Ester Sri (Jurnal Kajian Ekonomi dan Keuangan, 2009)
Indonesia has been implemented decentralization era since 2001 in order to increasing local empowerment and local capability. During this period central government gave a all of the authority to the local government excepted authority for the political, finance,national defence, justice and religion. Beside gave the authority to the local government, central government also gave the source of the financing to the local government to meet the money follows function principle. Financial stability is the most important things on the monetary area. Many theorytical background described that decentralization have relation with the local financial stability.Using statistic approach (panel data) we could be proved that decentralization have negative relation with the local financial stability and also the other variable such as population, GRDP, constriction price index and volatility of money